2009
DOI: 10.1007/s10549-009-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of GPR30 in the mechanisms of tamoxifen resistance in breast cancer MCF-7 cells

Abstract: Tamoxifen is the most frequently used anti-hormonal drug for treatment of women with hormone-dependent breast cancer. The aim of this study is to investigate the mechanism of tamoxifen resistance and the impact of the new estrogen G-protein coupled receptor (GPR30). MCF-7 cells were continuously exposed to tamoxifen for 6 months to induce resistance to the inhibitory effect of tamoxifen. These tamoxifen-resistant cells (TAM-R) exhibited enhanced sensitivity to 17-ss-estradiol and GPR30 agonist, G1, when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 33 publications
(49 reference statements)
7
128
0
3
Order By: Relevance
“…However, the authors stated that EGFR expression in combination with GPER-1 predicts lower survival in patients with ovarian cancer. This is in agreement with our recent results demonstrating that GPER-1 cross-talks with EGFR in breast cancer cell lines [22]. The cross-talk between GPER-1 and EGFR is associated with activation of completely different signalling pathways [5,6,23] and could be responsible for the observed difference in survival rates.…”
Section: Discussionsupporting
confidence: 93%
“…However, the authors stated that EGFR expression in combination with GPER-1 predicts lower survival in patients with ovarian cancer. This is in agreement with our recent results demonstrating that GPER-1 cross-talks with EGFR in breast cancer cell lines [22]. The cross-talk between GPER-1 and EGFR is associated with activation of completely different signalling pathways [5,6,23] and could be responsible for the observed difference in survival rates.…”
Section: Discussionsupporting
confidence: 93%
“…This may be a possible mechanism for tamoxifen resistance in some of the ER-positive breast cancers that express high levels of GPER. Consistently, overexpression of GPER in MCF7 breast cancer cells indeed increases tamoxifen resistance (49). Furthermore, there are clinical data showing that GPER is involved in tamoxifen resistance in breast cancer (12).…”
Section: Methodsmentioning
confidence: 63%
“…Some investigators have suggested that GPER1 contributes to tamoxifen resistance based on observations that tamoxifen stimulates GPER1 in vitro (10,11) and that GPER1 is upregulated in tamoxifen-resistant MCF7 cells (46). However, GPER1 has not appeared in functional screens for genes contributing to tamoxifen-resistance in breast cancer cells (47,48).…”
Section: Discussionmentioning
confidence: 99%